2008
DOI: 10.1345/aph.1k676
|View full text |Cite
|
Sign up to set email alerts
|

Ramelteon: A Novel Approach in the Treatment of Insomnia

Abstract: Ramelteon offers a novel mechanism of action for the treatment of insomnia. Studies support its short- and long-term use in adults and elderly adults for the treatment of primary insomnia characterized by difficulty with sleep initiation. Efficacy studies comparing ramelteon with other sleep agents are needed to further solidify the role of ramelteon in the treatment of insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Melatonin levels appear to decline with aging, and are lower in elderly insomniacs than in age‐matched controls. Ramelteon is the first melatonin receptor agonist approved by the FDA for the treatment of insomnia 102 . Ramelteon has high affinity for the MT 1 and MT 2 receptors located in the suprachiasmatic nucleus (SCN), which is responsible for generation and modulation of the circadian rhythm.…”
Section: Methodsmentioning
confidence: 99%
“…Melatonin levels appear to decline with aging, and are lower in elderly insomniacs than in age‐matched controls. Ramelteon is the first melatonin receptor agonist approved by the FDA for the treatment of insomnia 102 . Ramelteon has high affinity for the MT 1 and MT 2 receptors located in the suprachiasmatic nucleus (SCN), which is responsible for generation and modulation of the circadian rhythm.…”
Section: Methodsmentioning
confidence: 99%
“…The orexin system mainly promotes arousal; orexin antagonists have the potential to selectively promote sleep [27][28][29][30] and have fewer side effects [22]. Melatonin agonist drugs (eg, melatonin [31][32][33][34][35], ramelteon [36][37][38][39][40]) and antihistamine drugs (eg, diphenhydramine) [27][28][29][30] have also been studied extensively in recent years [41].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A2 is the primary isoenzyme responsible for ramelteon's metabolism to its major active metabolite, M‐II (Obach & Ryder, ). The concentration of M‐II in plasma is much higher, resulting in a 20‐ to 100‐fold greater overall mean systemic exposure than that of ramelteon (Reynoldson, Elliott, & Nelson, ). Despite the lower affinity, M‐II exhibited a selectivity for MT 1 and MT 2 receptors and the considerably higher blood levels showed that this metabolite might substantially contribute to ramelteon's overall activity (Greenblatt, Harmatz, & Karim, ; Pandiperumal et al, ).…”
Section: Introductionmentioning
confidence: 99%